A high‐flux automated laboratory small‐angle X‐ray scattering instrument optimized for solution scattering. Issue 1 (29th January 2021) - Lyngsø, Jeppe; Pedersen, Jan Skov
Abstract : Optimizations and characterization are described for a state‐of‐the‐art laboratory small‐angle X‐ray scattering instrument equipped with a Ga metal‐jet source at Aarhus University. Abstract : A commercially available small‐angle X‐ray scattering (SAXS) NanoSTAR instrument (Bruker AXS) with a liquid‐metal‐jet source (Excillum) has been optimized for solution scattering and installed at iNANO at Aarhus University. The instrument (named HyperSAXS) employs long high‐quality parabolic Montel multilayer optics (Incoatec) and a novel compact scatterless pinhole slit with Ge edges, which was designed and built at Aarhus University. The combination of the powerful source and optimized geometry gives an integrated X‐ray intensity close to 10 9  photons s −1 for a standard range of scattering vector moduli q = 0.0098–0.425 Å −1, where q = (4πsingθ)/λ and λ is the Ga  K α wavelength of 1.34 Å. The high intensity of the instrument makes it possible to measure dilute samples of, for example, protein or surfactant with concentrations of 1 mg ml −1 in a few minutes. A flow‐through cell, built at Aarhus University, in combination with an automated sample handler has been installed on the instrument. The sample handler is based on the commercial Gilson GX‐271 injection system (Biolab), which also allows samples to be stored under thermostatted conditions. The sample handler inserts and removes samples, and also cleans and dries the sample cell between measurements. The minimum volume of the flow‐through capillary is about 20 µl. The high intensity additionally allows time‐resolved measurements to be performed with a temporal resolution of seconds. For this purpose a stopped‐flow apparatus, (SFM‐3000, Bio‐Logic) was connected to the flow‐through cell by high‐performance liquid chromatography tubing. This configuration was chosen as it allows vacuum around the sample cell and thus maintains a low background. The instrument can readily be converted into a low‐ q setup with a q range of 0.0049–0.34 Å −1 and an X‐ray intensity of about 5 × 10 7  photons s −1 .